Mulheres honestas e mulheres faladas: uma questão de classe - Pedro, Joana Maria (Ed. da UFSC, 1994)
"Social history of turn-of-the-century Florianópolis explores prevailing stereotypes of women, how these contrasted with their actual situation, and how both changed with time and social pressures. Based on newspapers and archives, book is rich in detail but lacks conclusions"--Handbook of Latin American Studies, v. 58